Pengaruh Promosi Online, Persepsi Harga dan Citra Merek Terhadap Keputusan Pembelian Pada Restoran D’cost di Kalangan Masyarakat Kota Palembang - Syaputra, Darmawan; Larashati, Gabriel Vio (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to see how D’Cost can run its business with several marketing strategies, namely, Online Promotion, Price Perception and Brand Image. Quantitative methods are used to collect data by distributing questionnaires. The results of the analysis show that online promotion has a positive and significant effect on purchasing decisions. In addition, this study found that price perception has a significant positive and significant effect on purchasing decisions. And also, this study found that brand image has a positive and significant effect on purchasing decisions. The combination of Online Promotion strategies, Brand Image, and Good Price Perception together have a significant effect on consumer purchasing decisions. This shows the importance of integration between effective online promotions and building a good brand image with affordable prices to increase purchasing decisions. This research is expected to help academics and practitioners in understanding Online Promotion, Price Perception and Brand Image in an increasingly complex market era.